1985
DOI: 10.1107/s0108270185007843
|View full text |Cite
|
Sign up to set email alerts
|

Bond length and reactivity. Structure of 1-methoxymethoxy-3,5-dinitrobenzene, C8H8N2O6

Abstract: Abstract. M r = 228.17, orthorhombic, P212121, a = 5.387 (2), b= 11.053 (2), c= 16.783 (3)A, V= 999.3 (5)/k 3, Z = 4, D x = 1.516 (8) g cm -3, ,~(Mo Ka) = 0.71069 A,/2 = 1-0 cm -1, F(000) = 472, T= 293 K. R =0.041 for 1654 observed reflections. The C-O bond length to the leaving group (referred to acetal hydrolysis) is 1.431 (3)/k; this forms part of a linear correlation between bond length and reactivity in formaldehyde acetals MeOCH2-OR. The conformation about the acetal centre is close to (-sc,-sc) with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…6d, f and g). The NÁ Á ÁO intermolecular distance is below 3 Å and stays in very good agreement with previously studied crystals (Daszkiewicz, 2013b;Zhang et al, 2000;Jones et al, 1985;Hanson & Hitchcock, 2004;Popova et al, 1987;Klapö tke et al, 2009) and suggests an attraction between the nitro groups (Platts et al, 1995).…”
Section: Tablesupporting
confidence: 89%
See 1 more Smart Citation
“…6d, f and g). The NÁ Á ÁO intermolecular distance is below 3 Å and stays in very good agreement with previously studied crystals (Daszkiewicz, 2013b;Zhang et al, 2000;Jones et al, 1985;Hanson & Hitchcock, 2004;Popova et al, 1987;Klapö tke et al, 2009) and suggests an attraction between the nitro groups (Platts et al, 1995).…”
Section: Tablesupporting
confidence: 89%
“…A juxtaposition of the ring patterns showed that they are gradually expanded from the R 2 4 (8) ring. Overall, the nitro group can interact in many modes (Daszkiewicz, 2013b;Zhang et al, 2000;Jones et al, 1985;Hanson & Hitchcock, 2004;Popova et al, 1987;Klapö tke et al, 2009;Trzesowska-Kruszynska, 2015;Roy et al, 2015;Monta- Diversity of weak intermolecular interactions in (a) (H2m4na)NO 3 (1) and (b) (H2m4na)HSO 4 (2). zerozohori et al, 2015;Bauzá & Frontera, 2015;Gagnon et al, 2007;Tsuzuki et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 104 hits of 57 structures were found. For example, the O4⋯N2 close contact is seen on the normalized Hirshfeld surface 12,13 of 1-methoxymethoxy-3,5-dinitrobenzene 14 (Fig. 1a).…”
Section: Marek Daszkiewiczmentioning
confidence: 99%
“…1a was prepared by the acid-catalysed addition of the alcohol to 3,4-dihydro-2H-pyran. 14 dropwise sodium borohydride (0.185 g, 5 mmol) during 10 min at 0 ЊC. The mixture was stirred for 1 h at room temperature.…”
Section: -[22-bis(4-chlorophenyl)ethoxy]tetrahydropyran 1a [R ‫؍‬ (4-...mentioning
confidence: 99%